2006
DOI: 10.1002/pssc.200562715
|View full text |Cite
|
Sign up to set email alerts
|

Exciton self‐trapping in MEH‐PPV films studied by ultrafast emission depolarization

Abstract: Depolarization of the transient absorption with a time constant of <120 fs is observed in poly[2-(2'-ethylhexyloxy)-5-methoxy-1,4-phenylenevinylene] (MEH-PPV) film. It is too fast to be explained by incoherent hopping. We attribute it to dynamic localization (self-trapping) of the initially delocalized excitons driven by structural relaxation of excited segments. Implications for charge carrier photogeneration are briefly discussed.1 Introduction Conjugated polymers with a strong electronic coupling along thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
4
8
0
2
Order By: Relevance
“…Theoretical and transient absorption/emission studies have presented arguments both for and against exciton localization by conformational disorder in amorphous, solution-phase thiophene systems. , The observed large dynamic Stokes shifts are generally attributed to either (1) EET between disordered conjugated segments and/or (2) self-trapping dynamics resulting in planarization and conjugation extension. ,, Self-trapping, as discussed here, is defined as a monomolecular structural and/or vibrational relaxation resulting in the energetic stabilization of an exciton. Exciton localization was previously considered to result from stochastic excited-state self-trapping, as has been observed in other polymers like MEH-PPV. , However, two-color three-photon echo peak shift (2C-3PEPS) experiments, performed by Blank and co-workers, found that the initial (<200 fs) exciton relaxation in low-concentration P3HT in chloroform is highly correlated and not the result of random dynamics. Instead, the initial Stokes shift is driven by coherent low-frequency torsional excited-state self-trapping, which reorganizes the polymer to lower the free energy of the exciton and creates a local minimum, or trap, on the excited-state potential energy surface.…”
mentioning
confidence: 97%
“…Theoretical and transient absorption/emission studies have presented arguments both for and against exciton localization by conformational disorder in amorphous, solution-phase thiophene systems. , The observed large dynamic Stokes shifts are generally attributed to either (1) EET between disordered conjugated segments and/or (2) self-trapping dynamics resulting in planarization and conjugation extension. ,, Self-trapping, as discussed here, is defined as a monomolecular structural and/or vibrational relaxation resulting in the energetic stabilization of an exciton. Exciton localization was previously considered to result from stochastic excited-state self-trapping, as has been observed in other polymers like MEH-PPV. , However, two-color three-photon echo peak shift (2C-3PEPS) experiments, performed by Blank and co-workers, found that the initial (<200 fs) exciton relaxation in low-concentration P3HT in chloroform is highly correlated and not the result of random dynamics. Instead, the initial Stokes shift is driven by coherent low-frequency torsional excited-state self-trapping, which reorganizes the polymer to lower the free energy of the exciton and creates a local minimum, or trap, on the excited-state potential energy surface.…”
mentioning
confidence: 97%
“…Dynamical localization of the wave function of a transient vibrationally hot excited state has been previously studied on π conjugated polymers. Adiabatic vibrational relaxation of the lowest electronic excited state has been linked to the spatial localization (self-trapping) of an exciton strongly coupled to torsional and C–C nuclear motions. ,, The time-scale associated with such adiabatic process is relatively slow (ps) being defined by molecular vibrations and the flow of excess vibrational energy to the bath. Our previous measurements of the vibrational relaxation in several phenylene-ethynylene dendrimers yield a time constant of between 2 and 6 ps, while vibrational relaxation of the lowest excited state in polyfluorenes due to slow torsional motions can take up to tens of picoseconds resulting in a formation of self-trapped states …”
Section: Summary and Conclusionmentioning
confidence: 99%
“…[17][18][19] Pulse lasers with pulse durations of several tens to hundreds of femtoseconds were used to study MEH-PPV. [20][21][22] However, no study has been reported on the coherent molecular vibration induced by an impulsive excitation using a short enough pulse to excite coherent vibration.…”
mentioning
confidence: 99%